2015
DOI: 10.1177/1934578x1501000832
|View full text |Cite
|
Sign up to set email alerts
|

Chemical Composition of the Essential Oil from Chaerophyllum Temulum (Apiaceae)

Abstract: The present study reports the chemical composition on the essential oil obtained from fresh roots, stems, inflorescences and fruits of Chaerophyllum temulum. In all samples, except the roots, the most dominant components were sesquiterpene hydrocarbons. (Z)-Falcarinol was the principal constituent of the root essential oils (61.7% at the flowering stage and 62.3% at the fruiting stage). The blossom oil was dominated by (Z,E)-α-farnesene (23.4%), (E)-β-farnesene (9.0%) and germacrene D-4-ol (9%), whereas the oi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
4
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
4

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 21 publications
1
4
0
Order By: Relevance
“…It has been previously shown that the chemical compositions of essential oils isolated from different parts of the same species may differ to a significant level (Jovanović et al, 2015;Stamenković et al, 2015). This is in general agreement with the herein obtained results regarding HSes of different parts of the same species.…”
Section: Discussionsupporting
confidence: 93%
“…It has been previously shown that the chemical compositions of essential oils isolated from different parts of the same species may differ to a significant level (Jovanović et al, 2015;Stamenković et al, 2015). This is in general agreement with the herein obtained results regarding HSes of different parts of the same species.…”
Section: Discussionsupporting
confidence: 93%
“…temulum , as a part of our work on phytochemical analysis on genus Chaerophyllum , we have reported the composition of C . temulum essential oils, where the root contained the ( Z )‐falcarinol as principal component (over 60%), while in the essential oils of the aerial parts of the plant, this compound was found in relatively small amounts . Previous chemical investigations on the composition of the headspace volatiles and essential oils isolated from the leaves and fruits of C .…”
Section: Introductionmentioning
confidence: 99%
“…The biological activity of essential oils and extracts of some Chaerophyllum species such as antimicrobial, antioxidant, glutathione‐S‐transferase inhibitory activity and cytotoxic properties have been investigated.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Several investigations have been made on the essential oil composition of Chaerophyllum species [2][3][4][5][6][7][8][9][10][11][12][13][14][15][16]. Previous reports concerning the composition of the essential oil of C. hirsutum revealed that the composition of the oils obtained from different parts of Chaerophyllum hirsutum L. from Germany had the dominate presence of monoterpene hydrocarbons in all oils with up to 66% in the fruits, 38% in the leaves, 88% in the stems and 94% in the roots with smaller amounts of sesquiterpene hydrocarbons (up to 6% in the fruits, stems and roots and 28% in the leaves) [17].…”
mentioning
confidence: 99%